2019
DOI: 10.1029/2018jb016558
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Experimental Data on the Rheology of Olivine Aggregates

Abstract: Following the reanalysis of individual experimental runs of some widely cited studies (Jain et al., 2018, https://doi.org/10.1002/2017JB014847), we revisit the global data analysis of Korenaga and Karato (2008, https://doi.org/10.1029/2007JB005100) with a significantly improved version of their Markov chain Monte Carlo inversion. Their algorithm, previously corrected by Mullet et al. (2015) to minimize potential parameter bias, is further modified here to estimate more efficiently interrun biases in global da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 42 publications
(110 reference statements)
1
48
1
Order By: Relevance
“…Correlation coefficients are reported in Tables S2 and S3. a The error in V 2 and V 4 for model OL-WB 2 listed here is double the value reported in Jain et al (2019). This is because the high-pressure experimental data used in their study are expected to have larger than reported error; consequently the uncertainty in these parameters reported by Jain et al 2019 For the prescribed surface velocity, the width of our domain encompasses seafloor ages from 0 at the ridge to ∼85 Myr at x = 6,000 km ( Figure S1).…”
Section: Our Ridge Flow Modelmentioning
confidence: 80%
See 4 more Smart Citations
“…Correlation coefficients are reported in Tables S2 and S3. a The error in V 2 and V 4 for model OL-WB 2 listed here is double the value reported in Jain et al (2019). This is because the high-pressure experimental data used in their study are expected to have larger than reported error; consequently the uncertainty in these parameters reported by Jain et al 2019 For the prescribed surface velocity, the width of our domain encompasses seafloor ages from 0 at the ridge to ∼85 Myr at x = 6,000 km ( Figure S1).…”
Section: Our Ridge Flow Modelmentioning
confidence: 80%
“…For dislocation creep, probabilistic modeling yields values of 33 ± 5 (case S2d 10 ) and 29 ± 9 cm 3 mol −1 (case S2d eq ) for the activation volume under dry conditions, designated as V 3 . The a posteriori probability distributions of the successful models in our study ( Figures S4 and S5) indicate that both V 1 and V 3 are only loosely constrained, but these parameters were previously not constrained by the MCMC inversion of deformation data for lack of sufficient high-pressure experimental data under dry conditions (Jain et al, 2019).…”
Section: New Constraints On the Flow Law Parameters For Olivinementioning
confidence: 86%
See 3 more Smart Citations